A Control Method for Single-phase High-frequency Link Inverter - TU Fuquan; WU Songrong; WU Hao; ZHANG Xin (机车电传动)
In view of the condition that frequency converter switches of high-frequency link inverter SPWPM (sinusoidal pulse width and position modulation) working in high frequency had high losses, a new control method was studied. When the load power factor was closed to 1, frequency converter switches only needed to work in output voltage frequency, which reduced the switching losses of the converter effectively. Based on the single-phase push-pull type high-frequency link inverter topology, control and modulation methods were analyzed in detail. Combined with the frequency converter control, the double closed-loop control, outer voltage quasi PR (proportion resonant) control, and inner inductance current proportion control were studied. The simulation and experiment showed the reliability and feasibility of the control scheme.